Super Infection of Cutaneous Leishmaniasis Caused by Leishmania major and L. tropica to Crithidia fasciculata in Shiraz, Iran - Aliyar MIRZAPOUR; Alireza BADIRZADEH; Marzieh ASHRAFMANSOURI; Hamed BEHNIAFAR; Maryam NOROUZI; Hakim AZIZI; Mahmoodreza BEHRAVAN; Seyyed Javad SEYYED TABAEI (Tehran University of Medical Sciences, 2019)
Background: The aims of the current study were to determined present status of CL in Shiraz City, identify the causative species of Leishmania and conduct phylogenetic evaluations in detected parasites Methods: This study was conducted on 70 individuals with suspected CL that referred to the major health centers of Shiraz (Valfajr), Fars province, Iran, from Sep 2016 to Jul 2017. DNA was extracted from cultured Leishmania promastigotes and PCR-RFLP were performed using ITS1-rDNA gene. Results: Overall, 39 male (55.70%) and 31 (44.30%) female were found to be positive microscopically. All of direct examined positive samples were confirmed to be positive for Leishmania spp. DNA. Based upon the PCR-RFLP patterns and phylogenetic analysis, 46 (65.72%), 17 (24.28%) and 7 (10%) isolates were clearly identified as L. major, L. tropica and C. fasciculata, respectively. Conclusion: The dominat detected species in Shiraz City was L. major and L. tropica, respectively. CL has high prevalence in Shiraz City; therefore, more studies on leishmaniasis in the natural vectors and also reservoirs infection in this region is exceedingly recommended. Skin leisons due to C. fasciculata, was described for the first time in Iran (Shiraz City).